2011
DOI: 10.1016/j.compstruc.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the magnet support structure for the plasma fusion experiment Wendelstein 7-X

Abstract: a b s t r a c tThe world's largest plasma fusion experimental device of the stellarator family named Wendelstein 7-X (W7-X) [http://www.ipp.mpg.de/ippcms/eng/for/projekte/w7x/index.html] is being built at the MaxPlanck-Institute for Plasma Physics (IPP) in Greifswald, Germany. The mission of the experiment is to prove the fusion reactor relevance of the stellarator principle [1,2].Main subject of this paper is the description of the numerical simulation of the highly complex and multiple nonlinear W7-X magnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In particular, it has been shown that error fields with toroidal mode number n = 1 can overload divertor targets at relatively modest levels of (relative) error field amplitude. Such fields can arise from a variety of sources including coil assembly [3], ferritic materials, and superconducting coil motion [4]. To compensate such fields, five water cooled copper trim coils have been installed outside the cryostat of the device [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that error fields with toroidal mode number n = 1 can overload divertor targets at relatively modest levels of (relative) error field amplitude. Such fields can arise from a variety of sources including coil assembly [3], ferritic materials, and superconducting coil motion [4]. To compensate such fields, five water cooled copper trim coils have been installed outside the cryostat of the device [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This model was presented and studied in Ref. [21] and is a valuable model to identify the performance of the subspace iteration method.…”
Section: Solution Of Wheel Assemblagementioning
confidence: 98%
“…The approach includes intensive numerical studies with multiple parametric runs, taking into account the assembly tolerances achieved. Benchmarking between several independent FE global models was the key factor to eliminate all possible inaccuracies [31] and to define design values for each magnet system element. As a result, a tree of parametric FE models has been created and reused to support the assembly process of the machine and to assess proposed minor changes in the design and all reported non-conformities.…”
Section: Structural Stability Of the Superconducting Coil Systemmentioning
confidence: 99%